Concurrent infection by Clostridium perfringens type A, Clostridium septicum, and Clostridium sordelli in mouflon (Ovis aries musimon) - A case report - Milovanović, BZ; Đorđević, MM; Savić, BM; Jezdimirović, NV; Zdravković, NM; Zurovac-Sapundžić, Z; Glišić, D; Ninković, M; Kureljušić, B (Journal of the Hellenic Veterinary Medical Society, 2023)
A female mouflon, weighing 40 kilograms, was submitted to the diagnostic laboratory of the Institute of Veterinary Medicine of Serbia for determining the potential cause of death. Necropsy revealed massive hemorrhages in subcutaneous and intermuscular tissue and on papillary muscle. Petechiae and ecchymoses were found on the omentum, mesentery and adipose tissue of heart, kidney and costal pleura. Haemorrhagic-necrotic enteritis in duodenum and jejunum was characterized by catarrhal hemorrhagic inflammation with the presence of mucous and bloody content, whereas gas bubbles in the submucosa have also been confirmed. Bacterial cultures from sampled organs were identified as Clostridium perfringens type A, Clostridium septicum, and Clostridium sordelli. Based on the established pathological and histological changes and the results of the bacteriological, biochemical, and molecular examination, the state of septic shock and toxemia with disseminated massive bleeding was the immediate cause of mouflon death. The septic condition is a consequence of enterotoxemia caused by Clostridium perfringens type A, Clostridium septicum, and Clostridium sordelli infection.